Timing of Prophylactic Anticoagulation and Its Effect on Thromboembolic Events After Surgery for Metastatic Tumors of the Spine. Issue 11 (1st June 2019) - De la Garza Ramos, Rafael; Longo, Michael; Gelfand, Yaroslav; Echt, Murray; Kinon, Merritt D.; Yassari, Reza
Abstract : Study Design: Retrospective cohort study. Objective: To investigate the effect of timing of initiation of prophylactic anticoagulation (AC) on the incidence of venous thromboembolism (VTE) after surgery for metastatic tumors of the spine. Summary of Background Data: VTE is a known complication in patients undergoing surgery for metastatic spine disease. However, there is limited data on the use of prophylactic AC in this population and its impact on the risk of deep vein thrombosis (DVT) and pulmonary embolism (PE), as well as the risk of epidural hematoma. Methods: A retrospective review of our institutional neurosurgical spine database for the years 2012 through 2018 was performed. Patients who underwent surgery for metastatic tumors were identified. The development of VTE within 30 days was examined, as well as the occurrence of epidural hematoma. The incidence of VTE was compared between patients receiving "early" (within postoperative days 1–3) and "delayed" prophylactic AC (on or after postoperative day 4). Results: Sixty-five consecutive patients were identified (mean age 57, 62% male). The overall rate of VTE was 16.9%—all of whom had DVTs with a 3.1% rate of nonfatal PE (two patients also developed PE). From the overall cohort, 36 of 65 (56%) received prophylactic AC in addition to mechanical prophylaxis—22 in the early group (61.1%) and 14 in the delayed group (38.9%). The risk of VTE was 9.1% in the early group and 35.7% in the delayed group (26.6% absolute risk reduction; P  = 0.049); there was one case of epidural hematoma (1.5%). On multivariate analysis, delayed prophylactic AC was found to significantly increase the odds of VTE development (OR 6.43; 95% CI, 1.01–41.2; P  = 0.049). Conclusion: The findings of this study suggest that administration of prophylactic AC between days 1 and 3 after surgery for metastatic tumors of the spine may significantly reduce the risk of postoperative thromboembolic events. Level of Evidence: 4 Abstract : In this retrospective cohort study, the incidence of venous thromboembolism in patients who underwent surgery for metastatic tumors of the spine was investigated. Administration of prophylactic anticoagulation between days 1 and 3 after surgery significantly reduced the risk of postoperative thromboembolic events.